Oxygen Reduction Reaction Activity of Microwave Mediated Solvothermal Synthesized CeO2/g-C3N4 Nanocomposite - Soren, Siba; Hota, Ipsha; Debnath, A. K.; Aswal, D. K.; Varadwaj, K. S. K.; Parhi, Purnendu (Frontiers in Chemistry, 2019)
Electrocatalytic active species like transition metal oxides have been widely combined with carbon-based nanomaterials for enhanced Oxygen Reduction Reaction (ORR) studies because of the synergistic effect arising between different components. The aim of the present study is to synthesize CeO2/g-C3N4 system and compare the ORR activity with bare CeO2. Ceria (CeO2) embedded on g-C3N4 nanocomposite was synthesized by a single-step microwave-mediated solvothermal method. This cerium oxide-based nanocomposite displays enhanced ORR activity and electrochemical stability as compared to bare ceria.